THE USE OF EDUCATIONAL GAMES TO ENHANCE THE ENGLISH SKILL OF CHILDREN WITH SPECIAL NEEDS - Umi Ulfa Utami; Iin Inawati (Universitas Muhammadiyah Metro, 2022)
Realizing how vital English language education is today. Because children with special needs also have the right to learn like normal children, and because children with special needs will prefer games to games, the authors choose to use new teaching media in the form of educational games. The educational games used in this research are the Bingo alphabet, Charades, and Braille. Where all three are related to supporting students' abilities in learning English. This study aims to: Describe and analyze educational games and how they affect students. The author uses a case study method to describe and analyze three educational games at a private school in Tanjungpandan. The findings of this study are: (1) Students can improve their English skills through educational games that have several values that are by student learning which make the game more suitable to be used as a medium for learning English in the classroom for students. With special needs; (2) There are some visible results through the game. First, learning styles suit students so that they feel interested in learning. Second, motivation and background affect each student's learning progress, especially English.